Case report: An ectopic adrenocortical adenoma in the renal sinus - Liu, Tianyu; Lv, Renguang; Hu, Xiaolin; Li, Kewei; Ren, Qiangqiang; Zhang, Yongzhen; Meng, Liwei; Liu, Zhaoxu; Guo, Zhaoxin; Cheng, Yufeng (Frontiers in Oncology, 2022)
Background: Ectopic adrenal tissue is rare in adults, with an incidence of only about 1%. We report a rare case of ectopic adrenocortical adenoma in the left renal sinus. Case Presentation: A 57-year-old woman was admitted to the Department of Urology due to "a left kidney tumor" on physical examination. Multislice helical computed tomography (CT) showed the left kidney with an anterior lip mass near the hilum, approximately 2.3 × 2.2cm in size. Preoperative renal artery CTA showed no obvious abnormality. Laparoscopic resection of the left renal sinus mass was performed, and postoperative pathological findings showed ectopic adrenocortical adenoma. The tumor was a nonfunctional adenoma. Conclusion: Renal ectopic adrenal cortical adenoma is rare. Most of them are nonfunctional adenomas, which cannot be clearly diagnosed by preoperative imaging examination and can often be diagnosed by postoperative pathology.